Level of knowledge and attitude towards alzheimer`s disease among people in Sanglah General Hospital, Denpasar, Bali - Florence Diana Thomas; A.A. Bagus Ngurah Nuartha; I Putu Eka Widyadharma (DiscoverSys Inc., 2018)
Background: Alzheimer`s disease (AD) is a kind of dementia that causes impair of memory, intuition, and social life in elderly particularly. This study aims to know the public awareness, attitude, and knowledge of AD in Denpasar, BaliMethods: A cross-sectional study was conducted among 70 participants at Sanglah General Hospital by using self-administered questionnaire during April-May 2018 period. Subjects selection using simple random sampling method. Statistical analysis was carried out by using SPSS ver. 17 to know the percentage or proportion regarding with attitude and knowledge of AD.Results: About 39% of participants have a good knowledge, followed by 20% poor knowledge, and 41% don’t know about AD. The study found that 50% of participants have a good attitude, 25% poor attitude, and don’t have attitude regarding with AD. Data comparison showed that students scored higher for attitude than knowledge about 11%.Conclusion: Most of the participants at Sanglah General Hospital have a poor knowledge and attitude regarding with HD